2022
DOI: 10.1186/s13741-022-00278-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of opioid-sparing anesthesia regimen on short-term cognitive function after thoracoscopic surgery: a prospective cohort study

Abstract: Background As type of surgery and opioids are suggested risk factors for the development of cognitive decline after surgery, we evaluated the effect of an opioid-sparing anesthesia regimen involving preoperative erector spinae block and continuous infusion of flurbiprofen on the incidence of cognitive decline after video-assisted thoracoscopic surgery. Methods In this observational study, patients over 18 years old presenting for elective video-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Consistent with cognitive disorders like AD and MCI, and in addition to memory deficits, impairment in other cognitive domains is present in DNR. Many studies used neuropsychological tests to demonstrate visual cognitive dysfunction in DNR patients (Lage et al, 2021;Ji and Li, 2022;Zhao et al, 2022). We also found that the DNR patients showed poor performance postoperatively in visual attention, visual memory, visual-spatial scanning, and visual search speed assessed by DSST and TMT-A.…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with cognitive disorders like AD and MCI, and in addition to memory deficits, impairment in other cognitive domains is present in DNR. Many studies used neuropsychological tests to demonstrate visual cognitive dysfunction in DNR patients (Lage et al, 2021;Ji and Li, 2022;Zhao et al, 2022). We also found that the DNR patients showed poor performance postoperatively in visual attention, visual memory, visual-spatial scanning, and visual search speed assessed by DSST and TMT-A.…”
Section: Discussionmentioning
confidence: 58%
“…Zhao et al concluded that the application of ES block was associated with a marked decline in postoperative narcotic consumption after thoracoscopic surgery, and that helped to decrease postoperative cognitive dysfunction in such patients. 37 In our study, we found that the application of ES block in the perioperative period might have a potential beneficial impact on short-term and intermediate-term chronic pain and functional outcomes. The incidence of FBSS was significantly decreased in the block group, and consequently, functional scores were significantly improved.…”
Section: Discussionmentioning
confidence: 60%
“…The research frontiers were identified by analyzing the burst keywords The five most recent burst keywords were “recovery” “transcutaneous electrical acupoint stimulation” “systematic review” “quality” “general anesthesia” and “surgery.” Facilitating rehabilitation anesthesia management and reduction of opioid abuse has been a topic of interest in surgical departments ( 56 58 ). Despite progress in research more efforts are needed to understand the characteristics of the role of acupuncture anesthesia in rehabilitation sedation and mechanisms to reduce anesthetic drugs.…”
Section: Discussionmentioning
confidence: 99%